Quasi-experimental design in the application of an aerobic resistance program - Cortez Gutiérrez, Hernán Óscar; Cortez Gutiérrez, Milton Milcíades (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objectives were to determine the significant differences in the means of joint pain at two times in students. The difference between couples in quality of life is a normal distribution with Shapiro-Wilk statistic of 0.953 and significance of 0.451>0.05. The difference between joint pairs is not normal. Significant differences have been established between the means of pain after the application of an aerobic resistance program using the t-Student and Willcoxon statistical tests. In conclusion, the applied aerobic resistance program is effective for the reduction of joint pain.